1988
DOI: 10.1271/bbb1961.52.1233
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic production of ribavirin from pyrimidine nucleosides by Enterobacter aerogenes AJ 11125.

Abstract: Microorganisms that produce ribavirin(l-^-D-ribofuranosyl-l ,2,4-triazole-3-carboxamide; virazole®) directly from pyrimidine nucleosides and TCA(l,2,4-triazole-3-carboxamide) were screened from our stock cultures. Of the 400 strains tested, 16 were isolated as ribavirin-producers from uridine or cytidine. In particular, Enterobacter aerogenes AJ 1 1 125, Bacillus brevis AJ 1282 and Sarcina lutea AJ 1212 were found to possess potent activities of ribavirin production from them. In the presence of intact cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Like other mesophilic enzymes, the optimum temperature of these PNPs is almost above 65°C (Shirae et al 1988;Shirae and Yokozeki 1991). Many articles reported that cold-adapted enzymes from psychrophilic bacteria have higher catalytic activity and efficiency than their mesophilic counterparts at lower temperature (Lorentzen et al 2006;Li et al 2008;Zhang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other mesophilic enzymes, the optimum temperature of these PNPs is almost above 65°C (Shirae et al 1988;Shirae and Yokozeki 1991). Many articles reported that cold-adapted enzymes from psychrophilic bacteria have higher catalytic activity and efficiency than their mesophilic counterparts at lower temperature (Lorentzen et al 2006;Li et al 2008;Zhang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has broad spectrum and potent antiviral activity against DNA and RNA viruses. Currently, ribavirin can be produced by three methods: chemical synthesis, fermentation synthesis and enzymatic synthesis (Shirae et al 1988). However, chemical synthesis usually takes long time, requires harsh conditions and brings many by-products during the coupling reaction in industrial production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribavirin biotransformation was carried out using 1 × 10 9 colony-forming units (CFU), in 1 mL of reaction media containing equimolar concentrations (2.5 mM) of uridine (Urd) and TCA in sodium phosphate buffer (30 mM, pH 7). Reactions were performed during 16 h at 60 • C and 200 rpm as previously reported [13].…”
Section: Screeningmentioning
confidence: 99%
“…It is well known that there are some biocatalysts able to biosynthesize several nucleoside analogues [13,16]. Thus, 63 strains corresponding to 20 microbial genera were tested for ribavirin biotransformation (Scheme 1).…”
Section: Screeningmentioning
confidence: 99%